Airglow: Young People and Wellbeing (LEARNing Landscapes, 2024)
In this dialogue, Karl-André St-Victor and Dr. Jessica Ruglis discuss the concepts of wellbeing for youth and supporting young people in being well. Karl is the Executive Director of Chalet Kent, while Jessica is an Associate Professor of Human Development at McGill University and a Board Member at Chalet Kent. They have collaborated for the past eight years, and in this commentary, they discuss supporting the wellbeing of young people through two recent community projects: Que du Love (Only Love), a multimedia project; and the newly founded Uptown Institute, which aims to support young adults into flourishing lives. The dialogue is facilitated by Dr. Bronwen Low, Associate Professor of Education at McGill University and a long-standing partner and former Board President of Chalet Kent. The conversation touches on aspects of education, relationship building, trust, power, change, art, home, and the future.